Silicate slag combined with tebuconazole in management of brown eye spot in coffee - Lopes, Ueder Pedro; Zambolim, Laércio; Lopes, Uilton Nascimento; Rios, Jonas Alberto; Duarte, Henrique Silva Silveira; Ribeiro Júnior, José Ivo (Coffee Science - ISSN 1984-3909, 2013)
The aim of this trial was to evaluate silicon absorption and the effect of silicate slag application combined with triazole fungicide in control of brown eye leaf spot under greenhouse conditions, using coffee seedlings of the cultivar Catuaí Vermelho 144. A completely randomized 5x2 experimental design was used, with and without application of the fungicide tebuconazole, with eight replications. The mixtures (M) used on the soil were defined as based on the liming needs of the soil: M1- 0% de silicated slag (slag) and 100% limestone (lim); M2- 25% slag and 75% lim; M3-50% slag and 50% lim; M4- 75% slag and 25% lim; M5- 100% slag, with or without application of the fungicide tebuconazole. The fungicide tebuconazole (0.5 g of a.i./L) was applied on coffee seedlings through five pair of leaves. Twenty-four hours after fungicide application, each coffee seedling was inoculated with a conidial suspension of 2.0 x 105 /mL. The severity and the defoliation caused by disease were evaluated every five days from 20 to 45 days after inoculation. With the severity and defoliation data, the area under the brown eye spot disease progress curve (AUCPBES) and the area under the defoliation curve (AUCPDESF) were calculated. The application of increasing doses of silicate slag on the soil did not reduce AUCPBES and AUCPDESF, and no increase in Si content in the root, stem or leaf was observed. Tebuconazole reduced AUCPBES and AUCPDESF.